Giant ankyrin-B mediates transduction of axon guidance and collateral branch pruning factor sema 3A - Creighton, Blake A; Afriyie, Simone; Ajit, Deepa; Casingal, Cristine R; Voos, Kayleigh M; Reger, Joan; Burch, April M; Dyne, Eric; Bay, Julia; Huang, Jeffrey K; Anton, ES; Fu, Meng-Meng; et al. (eLife, 2021)
Variants in the high confident autism spectrum disorder (ASD) gene ANK2 target both ubiquitously expressed 220 kDa ankyrin-B and neurospecific 440 kDa ankyrin-B (AnkB440) isoforms. Previous work showed that knock-in mice expressing an ASD-linked Ank2 variant yielding a truncated AnkB440 product exhibit ectopic brain connectivity and behavioral abnormalities. Expression of this variant or loss of AnkB440 caused axonal hyperbranching in vitro, which implicated AnkB440 microtubule bundling activity in suppressing collateral branch formation. Leveraging multiple mouse models, cellular assays, and live microscopy, we show that AnkB440 also modulates axon collateral branching stochastically by reducing the number of F-actin-rich branch initiation points. Additionally, we show that AnkB440 enables growth cone (GC) collapse in response to chemorepellent factor semaphorin 3 A (Sema 3 A) by stabilizing its receptor complex L1 cell adhesion molecule/neuropilin-1. ASD-linked ANK2 variants failed to rescue Sema 3A-induced GC collapse. We propose that impaired response to repellent cues due to AnkB440 deficits leads to axonal targeting and branch pruning defects and may contribute to the pathogenicity of ANK2 variants.
Keywords: ankyrin; autism; growth cone; ANK2; axon branching; Sema 3a